The Effect of Flash Card Media Utilization on the Ability to Memorize Arabic Vocabulary in Grade IV Students of Madrasah Ibtidaiyah Raudhatul Mubtadiin - Syamsudin, Syamsudin; Silver, Soesiana Tri Eka; Utami, Sri (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to evaluate the effect of the use of flash card learning media on the ability to memorize Arabic vocabulary in grade IV students at Madrasah Ibtidaiyah Raudhatul Mubtadiin. Flash card learning media was chosen because it can accelerate understanding and strengthen students' memory through pictures or writing that lead to learning materials. The research method used is quantitative with a descriptive approach. The population of this study is all grade IV students at Madrasah Ibtidaiyah Raudhatul Mubtadiin, with a total of 25 students who are the research sample. The instruments used in this study are pretest and post-test using the T model, which aims to measure the ability to memorize Arabic vocabulary before and after the application of flash card media. The results of data analysis showed a significant improvement in the ability to memorize Arabic vocabulary after the use of flash card media. The post-test results showed a higher average score compared to the pretest score, with a significant difference according to the T test (t_hitung t_tabel, p 0.05). This indicates that flash card media is effective in improving the ability to memorize Arabic vocabulary in grade IV students at Madrasah Ibtidaiyah Raudhatul Mubtadiin.